The prevalence of cardiometabolic multimorbidity and its associations with health outcomes among women in China - Zhao, Yang; Zhang, Huan; Liu, Xiaoyun; Desloge, Allissa; Wang, Qian; Zhao, Siqi; Song, Lili; Tzoulaki, Ioanna (Frontiers in Cardiovascular Medicine, 2023)
Objective In China, a limited number of studies focus on women and examine the effect of cardiometabolic multimorbidity (defined as the presence of two or more cardiometabolic diseases) on health outcomes. This research aims to investigate the epidemiology of cardiometabolic multimorbidity and the association of cardiometabolic multimorbidity with long-term mortality. Methods This study used data from the China Health and Retirement Longitudinal Study between 2011 and 2018, which includes 4,832 women aged 45 years and older in China. Poisson-distributed Generalized Linear Models (GLM) were applied to examine the association of cardiometabolic multimorbidity with all-cause mortality. Results Overall, the prevalence of cardiometabolic multimorbidity was 33.1% among the total sample of 4,832 Chinese women, and increased with age, ranging from 28.5% (22.1%) for those aged 45–54 years to 65.3% (38.2%) for those aged ≥75 years in urban (rural) areas. Compared with the group of none and single disease, cardiometabolic multimorbidity was positively associated with all-cause death (RR = 1.509, 95% CI = 1.130, 2.017), after adjusting socio-demographic and lifestyle behavioral covariates. Stratified analyses revealed that the association between cardiometabolic multimorbidity and all-cause death was only statistically significant (RR = 1.473, 95% CI = 1.040, 2.087) in rural residents, but not significant in urban residents. Conclusion Cardiometabolic multimorbidity is common among women in China and has been associated with excess mortality. Targeted strategies and people-centered integrated primary care models must be considered to more effectively manage the cardiometabolic multimorbidity shift from focusing on single-disease.